Biochemical characteristics of extracts from proallergenic microfungi Erysiphe Palczewskii and Erysiphe convolvuli - Małgorzata Pac-Sosińska; Marta Palusińska-Szysz; Monika Sztandera-Tymoczek; Urszula Świderska; Sylwia Wdowiak-Wróbel; Agata Malinowska; Bianka Świderska; Agnieszka Szuster-Ciesielska (BMC Genomics, 2025)
Abstract Background Phytopathogenic microfungi Erysiphe palczewskii and Erysiphe convolvuli, are ectoparasites causing powdery mildew in common plants. Fungi often produce immunogenic factors triggering allergic reactions, with airborne protein allergens playing a pivotal role in respiratory allergies. This study delves into the biochemical characterization of E. palczewskii and E. convolvuli, focusing on their potential allergenic properties. Methods The composition of the tested fungi’s fatty acids and sugars was analyzed using liquid chromatography coupled with mass spectrometry (LC/MS). Protein extracts were also subjected to liquid chromatography-mass spectrometry analysis (LC/MS). Results The proteomic analysis of E. palczewskii identified 1118 peptides, with 68.8% unique to this species. The abundant proteins included ribosomal proteins, heat shock proteins, enolase, fumarate reductase, and nucleoside diphosphate kinase. The E. convolvuli analysis revealed 770 peptides, with 47% unique sequences. The abundant proteins included ribosomal proteins, heat shock proteins, NDPK, glycerol dehydrogenase, malate dehydrogenase, and a Rho GDP dissociation inhibitor. The analysis of the fatty acid composition revealed that both species exhibited a diverse profile and synthesized fatty acid 18:2, which constituted approximately 30% of the total fatty acids in E. palczewskii. The analyzed fungi primarily produced hexoses, pentoses, and hexosamines. Conclusion The comparative proteomic analysis provided insights into the unique and shared proteins of E. palczewskii and E. convolvuli. Several proteins, including heat shock proteins and enzymes involved in metabolic processes, exhibited allergenic potential. The studied fungi contained a high concentration of fatty acid 18:2, a precursor of arachidonic acid, which is involved in developing inflammatory responses.